LOGISTICS PROCESS MANAGEMENT USING ARTIFICIAL INTELLIGENCE OPTIMIZATION - Emeliane Gogilidze; Natia Gogilidze (International Journal of Innovative Technologies in Social Science, 2025)
Artificial Intelligence (AI) has been developing particularly fast recently and is becoming part of many areas of our daily lives. The development of artificial intelligence based on the Big Language Model has changed the job descriptions of many people. According to a Goldman Sachs study, generative AI will impact 300 million jobs, and according to a January 2023 study by platform Fishbowl, 43% of employees use AI in their professional lives. At the same time, such a rapid spread of AI is associated with some degree of danger for many. In March 2023, more than 1,000 people working in AI, including Ilon Musk, signed a petition calling for a 6-month moratorium on the development of large AI systems until their capabilities and associated threats are properly understood. Logistics is one industry where AI can have a transformative impact. It can be used in both the storage/transportation phases of product storage and consumption. AI can help address the challenges the sector faces today - managing logistics processes/optimizing production, managing demand, ensuring the sustainability of logistics systems, and simplifying the logistics transition, including reducing production and transportation costs.